2001
DOI: 10.1172/jci11076
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial coupling factor 6 as a potent endogenous vasoconstrictor

Abstract: We demonstrated recently that coupling factor 6, an essential component of the energy-transducing stalk of mitochondrial ATP synthase, suppresses the synthesis of prostacyclin in vascular endothelial cells. Here, we tested the hypothesis that coupling factor 6 is present on the cell surface and is involved in the regulation of systemic circulation. This peptide is present on the surface of CRL-2222 vascular endothelial cells and is released by these cells into the medium. In vivo, the peptide circulates in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…In clinical settings, we and others previously showed that circulating CF6 is elevated in patients with hypertension, acute myocardial infarction, end-stage renal disease, stroke and diabetes [13,14,[16][17][18], all of which predispose to the development of atherosclerosis. Given the present finding and the widespread biological actions of CF6, such as inhibition of prostacyclin and nitric oxide [21,[30][31][32][33], the reduction of CF6 levels may be an important and useful way to prevent cardiovascular events. To date, we have reported that salt restriction, vitamin C and vitamin B 12 plus folic acid lowered plasma levels of CF6 in patients with hypertension and stroke [13,17], and that peroxisome proliferator-activated receptor γ ligand attenuated CF6 release from cultured vascular endothelial cells [39].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In clinical settings, we and others previously showed that circulating CF6 is elevated in patients with hypertension, acute myocardial infarction, end-stage renal disease, stroke and diabetes [13,14,[16][17][18], all of which predispose to the development of atherosclerosis. Given the present finding and the widespread biological actions of CF6, such as inhibition of prostacyclin and nitric oxide [21,[30][31][32][33], the reduction of CF6 levels may be an important and useful way to prevent cardiovascular events. To date, we have reported that salt restriction, vitamin C and vitamin B 12 plus folic acid lowered plasma levels of CF6 in patients with hypertension and stroke [13,17], and that peroxisome proliferator-activated receptor γ ligand attenuated CF6 release from cultured vascular endothelial cells [39].…”
Section: Discussionmentioning
confidence: 81%
“…We further showed that CF6 attenuates prostacyclin generation by inhibiting cytosolic phospholipase A 2 [30] and nitric oxide generation via upregulation of asymmetric dimethylarginine or inhibition of endothelial nitric oxide synthase phosphorylation [31,32]. CF6 also elevates arterial blood pressure and enhances angiotensin IIinduced vasoconstriction in resistance arterioles [21,33]. In transgenic mice, intracellular pH measured by 31 P-MRS was reduced in skeletal muscle and liver, a finding consistent with the distribution of the receptor of CF6, the β-subunit of the ecto-F 1 F o complex.…”
Section: Discussionmentioning
confidence: 83%
“…The immunoreactive band for CXCR4 at 40-47kD was decreased in the TG hearts compared with the WT hearts, and the ratio of CXCR4 to CF6 decreased the gene and protein expression of CXCR4, but the decrease was only significant at a concentration of more than 10 -7 M. Like other vasoactive substances, the plasma CF6 level (10 -9 -10 -8 M) was lower than the critical concentration (10 -7 M) at which CXCR4 expression in cultured vascular endothelial cells was decreased in vitro (13,14). We previously showed that intravenous administration of anti-CF6 antibody to rats counteracted the biological effects of CF6 (15). Therefore, CF6 is active in vivo at a lower concentration compared with the concentration that was effective in vitro.…”
Section: Effect Of Cf6 On Hypoxia-induced Apoptosis In Huvecmentioning
confidence: 95%
“…Although HIF-1 acts as a transcriptional activator or repressor in a number of promoters (22,23), the CXCR4 promoter at HRE position -29 to -25 has been reported to be associated with CXCR4 repression (6). Thus, 15 one mechanism for CF6-induced CXCR4 repression is the binding of HIF-1 to the HRE at position -29 to -25 of the CXCR4 promoter.…”
Section: Regulation Mechanism For Cxcr4 Gene Expressionmentioning
confidence: 99%
“…4 Angiotensin II (Ang II), a representative proatherogenic molecule, was also reported to induce synthesis and secretion of sFlt-1 by nonhypoxic induction of the hypoxia-inducible transcription factor-a through AT 1 receptor pathways, but it was observed only in human trophoblasts, not in vascular endothelial cells. 5, 6 We recently showed that coupling factor 6 (CF6), a component of adenosine triphosphate (ATP) synthase, is present in the systemic circulation 7 and suppresses prostacyclin generation through inhibition of cytosolic phospholipase A 2 8 and NO generation by upregulating asymmetric dimethylarginine, an endogenous competitive inhibitor of NO synthase. 9 It is of interest that the molecular rotary motor F 1 F 0 complex, ATP synthase, is present in the plasma membrane, 10,11 and that endogenous prostacyclin and NO inhibitor CF6 forces the backward rotation of F 0 motor after binding to F 1 motor at the plasma membrane, resulting in intracellular acidosis.…”
Section: Introductionmentioning
confidence: 99%